The effect of the queen's age on the Varroa mite (Varroa destructor) burden of honey bee (Apis mellifera L.) colonies - Takács, Marianna; Oláh, János (Acta Agraria Debreceniensis, 2018)
An apiary trial was conducted in 2016 August to October in Szabolcs-Szatmár-Bereg County, Nyírmada to evaluate the influence of queen’s age on the Varroa destructor-burden in the treatment colonies. Sixty colonies of bees belonging to the subspecies Apis mellifera carnica pannonica in Hunor loading hives (with 10 frames in the brood chamber/deep super) were used. The colonies were treated with amitraz and the organophosphate pesticide coumaphos active ingredients. The amitraz treatment includes 6 weeks. The coumaphos treatment with Destructor 3.2% can be used for both diagnosis and treatment of Varroasis. For diagnosis, one treatment is sufficient. For control, two treatments at an interval of seven days are required. The colonies were grouped by the age of the queen: 20 colonies with one-year-old, 20 colonies with two-year-old and 20 colonies with three-year-old queen. The mite mortality of different groups was compared. The number of fallen mites was counted at the white bottom boards. The examination of spring growth of honey bee colonies has become necessary due to the judgement of efficiency of closing treatment. The data was recorded seven times between 16th March 2017 and 19th May 2017.Data on fallen mites were subjected to one-way analysis of variance (ANOVA) and Post-Hoc Tukey-test. Statistical analysis was performed using the software of IBM SPSS (version 21.). During the first two weeks after treatments, the number of fallen mites was significantly higher in the older queen’s colonies (Year 2014). The total mite mortality after amitraz treatment in the younger queen’s colonies was lower (P